SOCIAL REFLECTION MODEL TO IMPROVE TEACHERS' COMPETENCE - Maria Wulandari; Syafrianto SM; Kurniyati Kurniyati (Universitas Duta Bangsa Surakarta, 2021)
Reflection has recently been used in adult learning evaluation due to its humanistic value. However, in spite of its benefits, self-reflection has weaknesses for it is unshared. Self-reflection needs to be shared to colleagues, to be social reflection, so that it will be more beneficial for self-trough receiving feedback from others while others could also learn from it. Therefore, this article is going to report the study conducted to develop social reflection model to improve the teachers' competence. The model proposed is in the form of conceptual and iconic. The study employed R&D method proposed by Borg & Gall (1983). However, only parts of the steps were taken due to some limitations, those are research and information collecting, planning, developing preliminary product, and preliminary field testing, and main product revision. The result of the preliminary field testing shows that the model needs improvement.